Gender differences in overconfidence and decision-making in high-stakes competitions: Evidence from freediving contests - Mario Lackner; Hendrik Sonnabend (Johannes Kepler University of Linz, Department of Economics, 2020)
This study examines gender differences in overconfidence and decision-making in a high-stakes environment. Using data on more than 40,000 individual attempts from international freediving competitions, we provide evidence that women, on average, are less likely than men to overestimate their ability. This result is robust to different measures of overconfidence and can be partly explained by experience. There are no substantial gender differences on the intensive margin of overconfidence. In terms of performance, results suggest that women suffer more from overconfidence than men.
Keywords: D03; D81; J16; Z2; 330; overconfidence; gender; decision-making; competition; freediving